Persistent influence of obliquity on ice age terminations since the Middle Pleistocene transition - Bajo P.; Drysdale R. N.; Woodhead J. D.; Hellstrom J. C.; Hodell D.; Ferretti P.; Voelker A. H. L.; Zanchetta G.; Rodrigues T.; Wolff E.; Tyler J.; Frisia S.; et al. (Science, 2020)
Radiometric dating of glacial terminations over the past 640,000 years suggests pacing by Earth's climatic precession, with each glacial-interglacial period spanning four or five cycles of ∼20,000 years. However, the lack of firm age estimates for older Pleistocene terminations confounds attempts to test the persistence of precession forcing. We combine an Italian speleothem record anchored by a uranium-lead chronology with North Atlantic ocean data to show that the first two deglaciations of the so-called 100,000-year world are separated by two obliquity cycles, with each termination starting at the same high phase of obliquity, but at opposing phases of precession. An assessment of 11 radiometrically dated terminations spanning the past million years suggests that obliquity exerted a persistent influence on not only their initiation but also their duration.